2010
DOI: 10.1111/j.1399-6576.2009.02139.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of a combination of dexmedetomidine and hypothermia after incomplete cerebral ischemia in rats

Abstract: The combination of dexmedetomidine and hypothermia improved short-term neurologic outcome compared with the control group, whereas the combination therapy provided comparable neuroprotection with either of the two therapies alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
50
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 28 publications
1
50
1
2
Order By: Relevance
“…These data suggest that DEX administration either prior to or immediately following brain injury has no effect on brain water content or short-term neurological outcomes in surgical brain injury. A previous study showed significant neurological improvement in DEX-treated animals following stroke (88). However, one particular study showed no difference in neurological outcome (90), which may be due to the larger area of injury, which created a marked deficit in surgical brain injury compared with other models.…”
Section: Cerebral Injurymentioning
confidence: 92%
See 2 more Smart Citations
“…These data suggest that DEX administration either prior to or immediately following brain injury has no effect on brain water content or short-term neurological outcomes in surgical brain injury. A previous study showed significant neurological improvement in DEX-treated animals following stroke (88). However, one particular study showed no difference in neurological outcome (90), which may be due to the larger area of injury, which created a marked deficit in surgical brain injury compared with other models.…”
Section: Cerebral Injurymentioning
confidence: 92%
“…An increasing number of in vitro and in vivo studies indicates that DEX also exerts a cell-protective effect on nervous tissue under ischemic conditions (16,35,(85)(86)(87)(88). The relative safety of DEX administered as a sedative agent to neonatal animals was associated with the development of hippocampal synaptic functions.…”
Section: Cerebral Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…9 Recently, A number of studies have demonstrated that Dex treatment may confer neuroprotection against ischemic cerebral injury. [10][11][12] Dex has also been reported to improve neuron survival in animals subjected to cerebral ischemia/reperfusion injury. 11 In addition, both in vitro and in vivo evidence indicated that Dex could exert a cell-protective effect on nervous tissue under ischemic conditions.…”
mentioning
confidence: 99%
“…[10][11][12] Dex has also been reported to improve neuron survival in animals subjected to cerebral ischemia/reperfusion injury. 11 In addition, both in vitro and in vivo evidence indicated that Dex could exert a cell-protective effect on nervous tissue under ischemic conditions. 13 These neuroprotective effects of Dex against cerebral injury is associated with increasing the expression of brain-derived neurotrophic factors, stimulating astrocytic a 2 -adrenergic receptors and increasing astrocytic calcium concentrations.…”
mentioning
confidence: 99%